Mineral Nutrient Flow from an Inselberg in South-Western Nigeria - Isichei, Augustine O.; Morton, Alan J.; Ekeleme, Friday (2014)
In a study carried out to find out if inselbergs enrich their surroundings with nutrients via drainage, amounts of total nitrogen, nitrate-nitrogen and potassium in rainfall, drainage from bare rock patches and vegetation mats on an inselberg in South-western Nigeria were measured over one year. 43.3 kg ha-1 total nitrogen, 4.8 kg ha-1 nitrate-nitrogen and 10.7 kg ha-' potassium were recorded in rainfall for the year of study. The amount of total nitrogen in drainage from bare rock was 79% of that in rainfall whilst that in drainage from vegetation mats was 29% of the rainfall amount. The respective values for nitrate-nitrogen were 57% and 13%; for potassium they were 90% and 38%. It was assumed that the loss of nutrients as water drains through vegetation mats and over bare patches was due to absorption by plants and soil in the mats and lichens in the bare patches. It was therefore concluded that there was no net enrichment of rainwater with nutrients as it flows over inselberg slopes. There is, however, a funneling of water along with contained nutrients from the inselberg to the surrounding areas. This funneling is additional to the nutrients and rainfall incident on these surrounding areas and may account for the vegetation around inselbergs being more lush than vegetation in the same area but further away from the inselbergs. A simple modeling approach was used to assess potential nutrient outflow from inselbergs. The model shows that discharge of nutrients from the edges of inselbergs increases linearly with inselberg diameter. The model further shows that if nutrient funneling only affects an area near to the edge of the inselberg then nutrient addition is several times higher than would be expected from rainfall deposition alone.